Non-Pharmacological Approaches to the Prevention and Treatment of Alzheimer's Disease with Respect to the Rising Treatment Costs - Klimova, Blanka; Maresova, Petra; Kuca, Kamil (Current Alzheimer research, 2016)
Alzheimer's disease is a serious degenerative disease which is mainly typical of the developed countries. The prevalence percentage in Africa is only 2.6 %, whereas in America it is 6.5 % and in Western Europe 7.2 %. Overall, this disease affects 44 million people worldwide. With respect to the demographic development, a number of people suffering from Alzheimer's disease is expected in future. The key issue is not only the discovery of an effective medication, but also the early diagnosis, prevention and care about people with AD, as well as the provision of an equivalent rise of places in health and social institutions. Since the treatment of Alzheimer's disease (AD) imposes a severe economic and social burden, the main purpose of this study is to analyze and compare available non-pharmacological approaches to the prevention and treatment of patients with AD with special focus on their cognitive competences. In addition, the analysis also concentrates on the costs of pharmacological care in individual countries all over world. This is done by using Drummond's methodological approaches to direct and indirect costs. The analysis of non-pharmacological approaches is conducted on the basis of literature review of both clinical and review studies relevant for the research issue in the acknowledged databases and a comparison and evaluation of their findings.
Keywords: Global Health; celosvětové zdraví; náklady na zdravotní péči; Alzheimerova nemoc; Alzheimer Disease; analýza nákladů a výnosů; kognitivní poruchy; Male; lidé; Female; mužské pohlaví; ženské pohlaví; Cost-Benefit Analysis; Humans; Cognition Disorders; Health Care Costs